The Buy and Hold Investment Strategy: Building and Evaluating Passive Portfolios from Iraq Stock Exchange - Abdoun, Entidhar Lateef; Hasan, Mohammed Faez (Technium Business and Management, 2023)
This paper examines the buy and hold investment strategy, a passive approach where investors buy securities and hold them long-term regardless of market fluctuations. The rationale is that patient investors are rewarded over time despite short-term volatility. This research analyzes building and evaluating a buy and hold portfolio. First, a 12-stock portfolio across sectors is constructed using equal weighting and optimization during the Covid-19 pandemic. Equal weighting underperforms optimization that sets asset weights based on risk and return. Next, a 12-stock banking sector portfolio is built. Again, optimization improves results over equal weighting by accounting for risk and correlations. Though past performance does not guarantee future results, historically the buy and hold strategy has provided steady growth for long-term investors able to hold through downturns. Proper diversification and research are critical when constructing a buy and hold portfolio. While sacrificing potential short-term gains, this passive strategy aims to produce satisfying returns over the long run for investors with the appropriate temperament and perspective. However, the strategy may not suit those requiring active management or with lower risk tolerance.